Karakteristik Kitab Mazhraf Al-Basyir Karya KH. Baidhowi Kajen Pati - Saerozi, Ahmad (IIQ An Nur Yogyakarta, 2024)
This research discusses the characteristics of the book Mazhraf al-Basyir by KH. Baidhowi Kajen. KH. Baidhowi himself is a scholar whose lineage is connected to KH. Mutamakkin a famous Waliyullah from Kajen Pati. Mazhraf al-Basyir is one of the books in the field of ulumut tafsir. This research is motivated by the author's desire to know the characteristics of this book, given the very few scholars of the archipelago who authored works in the ulumut tafsir let alone using Arabic. Based on Zainul Milal's records, there are only 5 books of ulumut tafsir written by Nusantara scholars, one of which is Mazhraf al-Basyir. The purpose of this study is to determine the characteristics of the book Mazhraf al-Basyir and also to find out the extent of the contribution of this book to the study of ulumut tafsir. The method used is qualitative through literature study by reading recording and processing research materials.